Real-time control of automotive engine fuelled with Malaysian palm oil biodiesel - Azuwir, Mohd Nor; Mohd Zaki, Abdulmuin, Prof. Dr.; Abdul Hamid, Adom, Prof. Dr. (Praise Worthy Prize S.r.l., 2013)
Link to publisher's homepage at http://www.praiseworthyprize.com/